2002
DOI: 10.1289/ehp.02110s6971
|View full text |Cite
|
Sign up to set email alerts
|

Molecular circuits, biological switches, and nonlinear dose-response relationships.

Abstract: Signaling motifs (nuclear transcriptional receptors, kinase/phosphatase cascades, G-coupled protein receptors, etc.) have composite dose-response behaviors in relation to concentrations of protein receptors and endogenous signaling molecules. "Molecular circuits" include the biological components and their interactions that comprise the workings of these signaling motifs. Many of these molecular circuits have nonlinear dose-response behaviors for endogenous ligands and for exogenous toxicants, acting as switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 49 publications
0
23
0
1
Order By: Relevance
“…There has been substantial theoretical discussion (12,32,33) and experimental modeling (34)(35)(36)(37) regarding the possibility that individual genes are regulated in an on/off or in a graded manner in individual cells. Our study provides evidence that on/off switching occurs in cardiac myocytes and confirms other observations that individual genes change expression in an on/off rather than graded manner (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…There has been substantial theoretical discussion (12,32,33) and experimental modeling (34)(35)(36)(37) regarding the possibility that individual genes are regulated in an on/off or in a graded manner in individual cells. Our study provides evidence that on/off switching occurs in cardiac myocytes and confirms other observations that individual genes change expression in an on/off rather than graded manner (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances have demonstrated that molecular regulatory networks can be modelled in mathematical terms. Such approach will prevent hundreds of genotoxicological results and especially results from gene and protein arrays to serve simply as a catalogue of change (109).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The self-stimulation rate in the CDM model serves as a positive-feedback memory. Self-stimulation is a common property of master switches in gene regulation and other biological signaling systems [22,17,23,24]. In fact, the CDM is a candidate model of biological switches that exhibit multi-stability (co-existence of multiple stable equilibria) [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%